Preserving Maccera Tasi of Bugis Migrants in Bandar Lampung: The Transformation of Cultural Identity - Nururi, Imam; Yudianto, Asep; Fauzi, Ahmad (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2024)
This research is due to transmigration and cultural adaptation, where the movement of the Bugis community to Bandar Lampung required them to adapt their cultural traditions and practices to the new environment. This research is essential for uncovering cultural dynamics and the assimilation process and providing academic contributions and benefits to the Bugis community in Bandar Lampung. This research examines a cultural tradition, Maccera Tasi (sea alms ceremony), performed by the Bugis community in Bandar Lampung. Specifically, this study investigates whether this tradition has undergone a transformation and its role in preserving the Bugis cultural identity in diverse environments. This research employs a qualitative method with field research involving observation and interviews and an anthropological diffusion theory approach. The research results show that Maccera Tasi has experienced changes in the land of Lampung, such as implementation practices, meaning and symbolism, prayers and rituals, and socio-economic changes. Maccera Tasi is also the identity of the Bugis people who live in Bandar Lampung, so as an overseas ethnic minority, they can introduce the culture of sea parties to the broader community. The main findings show that this tradition is experiencing a process of Islamisation, integrating Islamic prayers and symbols with Islamic teachings. This study highlights the importance of understanding local context and external influences in cultural change and using diffusion theory to analyse the spread of cultural elements. This transformation allows overseas Bugis communities to maintain their cultural identity, strengthen communities and preserve cultural heritage.